Strategic Management in the Digital Age Unleashing Innovation and Resilience - Dlvin Sherzad Muhammed; Hazhar Omer Mohammed (QALAAI ZANIST JOURNAL, 2024)
In the digital age, strategic management is paramount for organizations to thrive amidst technological advancements and market complexities. This paper aims to investigate the impact of strategic planning on innovation and resilience in organizations. The main statistical result indicates a significant positive relationship between Strategy Formulation and Innovation, as well as Strategy Formulation and Resilience, with coefficients of determination of 18.1% and 42.3%, respectively. The study concludes that strategic management practices play a crucial role in fostering innovation and resilience, highlighting the importance of strategic leadership, digital skills, and a culture of experimentation. A total of 92 questionnaire forms were distributed among managers of department in these companies, eliciting 85 valid responses for analysis, resulting in an impressive response rate of 92.39%. Based on the findings, it is recommended that organizations prioritize strategic planning, continuous learning, and digital capabilities to enhance their competitive edge and adaptability in the digital era.